EVALUASI TINGKAT KESEHATAN KEUANGAN PADA PT ADHI KARYA (PERSERO) Tbk. TAHUN 2014-2016 - Sartika, Sartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study tries to evaluate the financial health of PT Adhi Karya (Persero) Tbk. in the period of 2014 - 2016. The object of this study is PT Adhi Karya (Persero) Tbk.. The data of this study are documentations of the companyâ€™s periodic financial statements from 2014 to 2016. The analysis on the companyâ€™s financial health is based on the Decree of Minister of State Owned Enterprises number KEP-100/MBU/2002, which mentions the eight indicators of financial health; they are Return On Equity, Return On Investment, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, Total Assets Turn Over and Total Ratio of Own Capital to Total Assets. The result of the analysis shows that PT Adhi Karya (Persero) Tbk. is financially â€œhealthyâ€ with the predicate of A.Keyword: Evaluation of Financial Health, Financial Statement, Financial Ratio.